Resin composition and molded article
By compounding acid-modified polyolefins in polyamide resin, the problem of slow crystallization at lower temperatures is solved, and the flexibility and impact resistance are improved, and crystallization is promoted at lower temperatures.
Patent Information
- Application Number
- CN202380055594.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-25
- Filing Date
- 2023-06-19
- Publication Date
- 2025-03-11
AI Technical Summary
The molded products of polyamide resin have shortcomings in terms of flexibility and impact resistance, especially at lower temperatures, and the crystallization speed is slower.
By compounding acid-modified polyolefins and phthalamine-based polyamide resins, a specific resin composition is formed, which improves its flexibility and impact resistance, and promotes crystallization at lower temperatures.
A polyamide resin composition that achieves rapid crystallization at lower temperatures has excellent softness and impact resistance, and is suitable for a variety of uses.
Smart Images

Figure BDA0005253421990000201 
Figure BDA0005253421990000202 
Figure BDA0005253421990000211
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and a molded product, and in particular to a resin composition with a polyamide resin as a main component. Background Art
[0002] Resin molded products are used for the purpose of reducing the weight and cost of metal molded products. In particular, polyamide resins, which have excellent properties such as heat resistance, chemical resistance, rigidity, wear resistance, and moldability, are used in various applications.
[0003] However, polyamide resin molded products have problems with flexibility and impact resistance depending on the application. Therefore, as a method for improving the flexibility and impact resistance of polyamide resins, there is a proposal to mix impact-resistant improving materials such as polyolefins (Patent Document 1, etc.).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 09-087475 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, if different types of resins such as polyolefins are mixed in order to improve the flexibility and impact resistance of polyamide resins, the crystallization rate tends to be slow. In particular, it is beneficial to increase the crystallization rate even when the mold is at a low temperature.
[0009] The present invention was made in order to solve the above problems, and an object of the present invention is to provide a polyamide resin composition and a molded article which are excellent in flexibility and impact resistance and can fully crystallize even at a relatively low temperature.
[0010] Solutions for solving problems
[0011] Based on the above problems, the present inventors have conducted intensive studies and found that the above problems can be solved by blending a predetermined polyamide resin acid-modified polyolefin. Specifically, the above problems were solved by the following means.
[0012] <1> A resin composition comprising 0.1 to 50 parts by mass of an acid-modified polyolefin relative to 100 parts by mass of a polyamide resin,
[0013] The polyamide resin comprises a diamine unit and a dicarboxylic acid unit, wherein the diamine unit comprises 70 mol% or more of a structural unit derived from xylylenediamine, and the dicarboxylic acid unit comprises 70 mol% or more of a structural unit derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms.
[0014] <2> according to <1> The resin composition, wherein 70 mol % or more of the dicarboxylic acid units are derived from dodecanedioic acid and / or tetradecanedioic acid.
[0015] <3> according to <1> The resin composition, wherein 70 mol % or more of the dicarboxylic acid units are derived from dodecanedioic acid.
[0016] <4> according to <1> ~ <3> The resin composition described above, wherein 20 to 100 mol % of the diamine units are derived from m-xylylenediamine, and 80 to 0 mol % are derived from p-xylylenediamine.
[0017] <5> according to <1> The resin composition, wherein 70 mol% or more of the dicarboxylic acid units are derived from dodecanedioic acid and / or tetradecanedioic acid,
[0018] 20 to 100 mol% of the diamine units are derived from m-xylylenediamine, and 80 to 0 mol% are derived from p-xylylenediamine.
[0019] <6> according to <1> ~ <5> The resin composition described in any one of the preceding claims, wherein the acid-modified polyolefin comprises a maleic anhydride-modified polyolefin.
[0020] <7> A molded product, which is composed of <1> ~ <6> The resin composition described in any one of the above is formed.
[0021] Effects of the Invention
[0022] According to the present invention, a polyamide resin composition and a molded article which are excellent in flexibility and impact resistance and in which crystallization proceeds sufficiently even at a relatively low temperature can be provided. DETAILED DESCRIPTION
[0023] Hereinafter, a mode for implementing the present invention (hereinafter, simply referred to as "this embodiment") will be described in detail. It should be noted that the following this embodiment is an example for explaining the present invention, and the present invention is not limited to this embodiment.
[0024] In addition, in this specification, "to" is used to mean that the numerical value described before and after it is included as a lower limit and an upper limit.
[0025] In this specification, various physical property values and characteristic values are assumed to be values at 23° C. unless otherwise specified.
[0026] In this specification, the number average molecular weight can be measured according to the description of paragraph 0047 of JP-A-2018-165298 unless otherwise specified, and the content thereof is incorporated into this specification.
[0027] In this specification, unless otherwise specified, the melting point (Tm) is described as a value measured by differential scanning calorimetry (DSC) in accordance with ISO 11357. Specifically, it can be measured according to the description of paragraph 0036 of International Publication No. 2016 / 084475, and the content thereof is incorporated into this specification.
[0028] When the measurement methods and the like described in the specifications shown in this manual differ by year, they are based on the specifications as of January 1, 2022 unless otherwise specified.
[0029] The resin composition of the present embodiment is characterized in that it contains an acid-modified polyolefin in a ratio of 0.1 to 50 parts by mass relative to 100 parts by mass of a polyamide resin, wherein the polyamide resin contains a diamine unit and a dicarboxylic acid unit, the diamine unit contains 70 mol% or more of a structural unit derived from xylylenediamine, and the dicarboxylic acid unit contains 70 mol% or more of a structural unit derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms.
[0030] By forming such a structure, a polyamide resin composition having excellent flexibility and impact resistance and capable of fully crystallizing even at relatively low temperatures can be obtained. In particular, a resin composition having excellent impact resistance under cold or hot conditions can be obtained. Furthermore, a resin composition having excellent moldability, a small amount of eluted matter, and excellent chemical resistance can be obtained.
[0031] Usually, if different kinds of resins such as polyolefins are blended in a polyamide resin, there is a tendency for the crystallization rate to decrease. However, in the present invention, surprisingly, by blending an acid-modified polyolefin in a prescribed xylenediamine-based polyamide resin, the crystallization rate is improved. It is speculated that the reason is that by using an acid-modified polyolefin, the acid group possessed by the polyolefin reacts with the amide group at the end of the xylenediamine-based polyamide resin. That is, it is speculated that the reaction site becomes the starting point and crystallization is promoted. It is also speculated that the length of the aliphatic chain of the xylenediamine-based polyamide resin used in the present embodiment acts in a good direction on compatibility with polyolefins, etc. In particular, as shown in the embodiments described later, in the polyamide resin synthesized by xylenediamine and sebacic acid (carbon number 10), the crystallization rate is poor, so the effect of the present invention should be extremely surprising.
[0032] <Xylylenediamine-based polyamide resin>
[0033] The resin composition of the present embodiment includes a polyamide resin (sometimes referred to as "xylylenediamine-based polyamide resin" in this specification), wherein the polyamide resin includes a diamine unit and a dicarboxylic acid unit, wherein the diamine unit includes 70 mol% or more of a structural unit derived from xylylenediamine, and the dicarboxylic acid unit includes 70 mol% or more of a structural unit derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms. By using a xylylenediamine-based polyamide resin, a resin composition having a high crystallization rate can be obtained even when a polyolefin is blended.
[0034] Of the diamine-derived structural units of the xylylenediamine-based polyamide resin, more preferably 75 mol% or more, further preferably 80 mol% or more, further preferably 90 mol% or more, still further preferably 95 mol% or more, and particularly preferably 99 mol% or more are derived from xylylenediamine (preferably p-xylylenediamine and / or m-xylylenediamine).
[0035] In xylylenediamine, more specifically, preferably 20 to 100 mol% of the structural units derived from diamine are structural units derived from meta-xylylenediamine, preferably 50 to 100 mol% of the structural units derived from diamine are structural units derived from meta-xylylenediamine, more preferably 55 to 80 mol% of the structural units derived from diamine are structural units derived from meta-xylylenediamine, and 45 to 20 mol% of the structural units derived from diamine are structural units derived from p-xylylenediamine. By making the proportion of p-xylylenediamine 20 mol% or more, the crystallization rate becomes faster, and there is a tendency that the impact resistance of the obtained molded article is improved. In addition, by reducing the proportion of meta-xylylenediamine, the amount of eluted matter from the molded article can be reduced.
[0036] In the xylylenediamine-based polyamide resin, the total amount of the structural units derived from p-xylylenediamine and the structural units derived from m-xylylenediamine preferably accounts for 80 mol% or more of the structural units derived from diamine, more preferably 85 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, further preferably 98 mol% or more, and further preferably 99 mol% or more. The upper limit of the total amount of the structural units derived from p-xylylenediamine and the structural units derived from m-xylylenediamine is 100 mol%.
[0037] Examples of diamines other than meta-xylylenediamine and para-xylylenediamine that can be used as the raw material diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, and 1,3- Alicyclic diamines such as bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane, and diamines having an aromatic ring such as bis(4-aminophenyl)ether, p-phenylenediamine, and bis(aminomethyl)naphthalene can be used alone or in combination of two or more.
[0038] On the other hand, of the structural units derived from dicarboxylic acid in the xylylenediamine-based polyamide resin, preferably 75 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, and particularly preferably 99 mol% or more are derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms (preferably an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 15 carbon atoms, and more preferably an α,ω-straight-chain aliphatic dicarboxylic acid having 12 to 14 carbon atoms).
[0039] Examples of the α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms preferably used as the raw material dicarboxylic acid component of the xylylenediamine-based polyamide resin include undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, octadecanedioic acid, nonadecanedioic acid, and eicosanedioic acid. One or more of them may be used. Among these, dodecanedioic acid and / or tetradecanedioic acid are preferred.
[0040] As a preferred embodiment of the xylylenediamine-based polyamide resin in the present embodiment, 70 mol% or more (preferably 80 mol% or more, more preferably 90 mol% or more, and further preferably 95 mol% or more) of the structural units derived from dicarboxylic acid are derived from dodecanedioic acid and / or tetradecanedioic acid (preferably dodecanedioic acid). Dodecanedioic acid and xylylenediamine may also be raw materials derived from organisms (biomass raw materials).
[0041] Furthermore, in the above embodiment, preferably 20 to 100 mol% of the diamine units are derived from m-xylylenediamine and 80 to 0 mol% are derived from p-xylylenediamine, and more preferably 55 to 80 mol% of the diamine units are derived from m-xylylenediamine and 45 to 20 mol% are derived from p-xylylenediamine.
[0042] Examples of the dicarboxylic acid component other than the above-mentioned α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms include phthalic acid compounds such as isophthalic acid, terephthalic acid, and phthalic acid, and isomers of naphthalene dicarboxylic acids such as 1,2-naphthalene dicarboxylic acid, 1,3-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 1,7-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, and 2,7-naphthalene dicarboxylic acid. These can be used alone or in combination of two or more.
[0043] It should be noted that the xylenediamine-based polyamide resin is composed of structural units derived from diamines and structural units derived from dicarboxylic acids as main components, but structural units other than these are not completely excluded, and of course, structural units derived from aliphatic aminocarboxylic acids such as lactams such as ε-caprolactam, laurolactam, aminocaproic acid, and aminoundecanoic acid may also be included. The main component here refers to that among the structural units constituting the xylenediamine-based polyamide resin, the total count of the structural units derived from diamines and the structural units derived from dicarboxylic acids is the largest among all structural units. In the present embodiment, the total of the structural units derived from diamines and the structural units derived from dicarboxylic acids in the xylenediamine-based polyamide resin preferably accounts for more than 90% by mass of all structural units, more preferably more than 95% by mass, further preferably more than 97% by mass, and further preferably more than 99% by mass.
[0044] The melting point of the xylylenediamine polyamide resin is preferably 180°C or higher, more preferably 190°C or higher, further preferably 195°C or higher, further preferably 200°C or higher, and may be 201°C or higher. It is preferably 280°C or lower, more preferably 240°C or lower.
[0045] The lower limit of the number average molecular weight (Mn) of the xylylenediamine polyamide resin is preferably 6,000 or more, more preferably 8,000 or more, and further preferably 10,000 or more, and is preferably 35,000 or less, more preferably 30,000 or less, and further preferably 25,000 or less. Within such a range, heat resistance, elastic modulus, dimensional stability, and molding processability become better.
[0046] The content of the xylenediamine polyamide resin in the resin composition of the present embodiment is preferably 50% by mass or more, more preferably 55% by mass or more, further preferably 60% by mass or more, and further preferably 64% by mass or more in the resin composition, and can be 70% by mass or more. By being set to above the aforementioned lower limit, there is a tendency for improved moldability. In addition, the content of the xylenediamine polyamide resin in the resin composition of the present embodiment is preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 85% by mass or less, and further preferably 80% by mass or less in the resin composition. By being set to below the aforementioned upper limit, there is a tendency for improved impact resistance and faster crystallization rate.
[0047] The resin composition of the present embodiment may contain only one type of xylylenediamine-based polyamide resin, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.
[0048] The resin composition of the present embodiment may contain other polyamide resins other than the xylylenediamine-based polyamide resin within the scope of the present invention.
[0049] The other polyamide resin is not particularly limited, and a known polyamide resin can be used. The polyamide resin may be an aliphatic polyamide resin or a semi-aromatic polyamide resin.
[0050] Examples of the aliphatic polyamide resin include polyamide 4, polyamide 46, polyamide 6, polyamide 66, polyamide 666, polyamide 610, polyamide 612, polyamide 11, and polyamide 12.
[0051] Examples of the semi-aromatic polyamide resin include terephthalic acid-based polyamide resins (polyamide 6T, polyamide 9T, polyamide 10T, polyamide 6I6T), and polyamide resins composed of xylylenediamine and an α,ω-straight-chain aliphatic dicarboxylic acid having less than 10 carbon atoms (MXD6, MP6, etc.).
[0052] When these other polyamide resins are contained, they are preferably contained in a ratio of 0.1 to 10% by mass of the resin composition.
[0053] In addition, in the resin composition of the present embodiment, the total amount of the xylylenediamine-based polyamide resin and the acid-modified polyolefin preferably accounts for 90% by mass or more of the resin composition, more preferably 95% by mass or more, further preferably 96% by mass or more, further preferably 97% by mass or more, and further preferably 98% by mass or more.
[0054] <Acid-modified polyolefin>
[0055] The resin composition of the present embodiment contains the acid-modified polyolefin in a ratio of 0.1 to 50 parts by mass relative to 100 parts by mass of the polyamide resin. By containing the acid-modified polyolefin, the flexibility and impact resistance of the obtained molded article can be improved.
[0056] The acid-modified polyolefin used in the present embodiment is obtained, for example, by acid-modifying a polyolefin. Acid modification means that an acid derivative is reacted with a polyolefin in any form. Specifically, the acid-modified polyolefin used in the present embodiment is obtained by grafting an acid derivative onto the main chain of a polyolefin or incorporating an acid derivative into the main chain of a polyolefin. In the present embodiment, the polyolefin is preferably a graft polymer in which an acid derivative is grafted onto the main chain of a polyolefin.
[0057] The acid derivative is preferably an acid or an anhydride, more preferably an unsaturated carboxylic acid or an anhydride of an unsaturated carboxylic acid, and still more preferably an anhydride of an unsaturated carboxylic acid. The unsaturated carboxylic acid is preferably an unsaturated dicarboxylic acid, and the anhydride of an unsaturated carboxylic acid is also preferably an anhydride of an unsaturated dicarboxylic acid.
[0058] As the acid derivative, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, 5-norbornene-2,3-dicarboxylic acid, 5-norbornene-2,3-dicarboxylic anhydride, norbornene dicarboxylic acid, endicanhydride, citraconic acid, citraconic anhydride, 1-butene-3,4-dicarboxylic acid, and 1-butene-3,4-dicarboxylic anhydride are more preferred, maleic acid and maleic anhydride are further preferred, and maleic anhydride is still more preferred.
[0059] The method of modifying the copolymer with an acid derivative can be carried out by a known technique without particular limitation, and for example, the following methods can be used: a method of copolymerizing an acid derivative with a monomer serving as a raw material of the copolymer, a method of grafting an acid derivative onto the copolymer, etc.
[0060] In addition, in the resin composition of this embodiment, the xylylenediamine-based polyamide resin and the acid-modified polyolefin may be bonded to each other.
[0061] The acid-modified polyolefin is preferably obtained by acid-modifying a copolymer including a structural unit derived from ethylene and a structural unit derived from an α-olefin having 3 to 20 carbon atoms with an acid derivative. By forming such a structure, impact resistance can be more effectively improved.
[0062] The α-olefin having 3 to 20 carbon atoms is preferably an α-olefin having 3 to 10 carbon atoms, more preferably an α-olefin having 3 to 8 carbon atoms, further preferably an α-olefin having 3 to 5 carbon atoms, and still more preferably an α-olefin having 3 or 4 carbon atoms. Specific examples of the α-olefins having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 9-methyl-1-decene, 11-methyl-1-dodecene, and 12-ethyl-1-tetradecene, and propylene and 1-butene are preferred.
[0063] The copolymer comprising structural units derived from ethylene and structural units derived from an α-olefin having 3 to 20 carbon atoms may contain only one type of repeating unit derived from an α-olefin having 3 to 20 carbon atoms, or may contain two or more types. The copolymer may be a random polymer or a block polymer.
[0064] The copolymer preferably contains structural units derived from an α-olefin having 3 to 20 carbon atoms in a ratio of 6 to 25 mol % of all structural units, more preferably 8 to 22 mol %, and even more preferably 10 to 20 mol %. Such a structure can more effectively improve impact resistance.
[0065] The copolymer preferably contains structural units derived from ethylene in a ratio of 94 to 75 mol %, more preferably 92 to 78 mol %, and even more preferably 90 to 80 mol % of all structural units.
[0066] Furthermore, the copolymer may contain other structural units in addition to the structural units derived from ethylene and the structural units derived from α-olefins having 3 to 20 carbon atoms. When the acid-modified polyolefin used in the present embodiment contains other structural units, the proportion is preferably 10 mol% or less of all the structural units in the copolymer.
[0067] Specific examples of the copolymer include ethylene / propylene copolymers, ethylene / butene copolymers, ethylene / hexene copolymers, ethylene / propylene / dicyclopentadiene copolymers, and ethylene / propylene / 5-ethylidene-2-norbornene copolymers, and ethylene / butene copolymers are preferred.
[0068] An example of the acid-modified polyolefin used in the present embodiment is a maleic anhydride-modified polyolefin, preferably an ethylene / propylene copolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, an ethylene / propylene / dicyclopentadiene copolymer or an ethylene / propylene / 5-ethylidene-2-norbornene copolymer modified with maleic anhydride.
[0069] The acid modification rate of the acid-modified polyolefin used in the present embodiment is preferably 0.3% by mass or more, more preferably 0.4% by mass or more, further preferably 0.5% by mass or more, further preferably 0.6% by mass or more, further preferably 0.8% by mass or more, and particularly preferably 0.9% by mass or more. By setting it to such a range, the impact resistance can be improved more effectively. On the other hand, as the upper limit of the acid modification rate, it is preferably 4.0% by mass or less, more preferably 3.5% by mass or less, further preferably 3.0% by mass or less, and further preferably 2.5% by mass or less. By setting it below the upper limit, there is a tendency for the dispersibility of the acid-modified polyolefin to be improved.
[0070] In addition, the modification rate by an acid derivative (acid modification rate) in this embodiment is measured according to the description of paragraph 0056 of JP-A-2018-087319.
[0071] Examples of commercially available products of the acid-modified polyolefin used in the present embodiment include TAFMER (trade name, graft polymer) manufactured by Mitsui Chemicals, FUSABOND (trade name) manufactured by DuPont, and Amplify (trade name) manufactured by TAU.
[0072] The content of the acid-modified polyolefin in the resin composition of the present embodiment is relative to 100 mass parts of polyamide resin, and is more than 0.1 mass parts, preferably more than 1 mass parts, more preferably more than 5 mass parts, more preferably more than 8 mass parts, and then preferably more than 10 mass parts, and then more preferably more than 12 mass parts, and then more preferably more than 14 mass parts, and can also be more than 16 mass parts, more than 22 mass parts.By being set to more than the aforementioned lower limit, there is a tendency that the impact resistance and flexibility of the molded article obtained are further improved.In addition, the content of the aforementioned acid-modified polyolefin is relative to 100 mass parts of polyamide resin, and is less than 50 mass parts, preferably less than 45 mass parts, more preferably less than 40 mass parts, more preferably less than 35 mass parts, and then preferably less than 30 mass parts.By being set to less than the aforementioned upper limit, there is a tendency that moldability improves.
[0073] The resin composition of the present embodiment may contain only one acid-modified polyolefin or two or more acid-modified polyolefins. When two or more acid-modified polyolefins are contained, the total amount is preferably within the above range.
[0074] <Plasticizer>
[0075] The resin composition of the present embodiment may contain a plasticizer. By containing a plasticizer, flexibility tends to be improved.
[0076] Examples of the plasticizer include amide plasticizers, ester plasticizers, and amide ester plasticizers, and amide plasticizers are preferred.
[0077] Examples of the amide plasticizer include carboxylic acid amide plasticizers and sulfonamide plasticizers. Examples of the carboxylic acid amide plasticizer include amides of one or more acids selected from the group consisting of benzoic acid, phthalic acid, trimellitic acid, pyromellitic acid, and their anhydrides and dialkylamines having an alkyl group with a carbon number of 2 to 8. In addition, examples of the dialkylamines having an alkyl group with a carbon number of 2 to 8 include diethylamine, dipropylamine, dibutylamine, dihexylamine, di(2-ethylhexyl)amine, and dioctylamine.
[0078] The plasticizer used in the present embodiment is preferably N-butylbenzenesulfonamide, N-(2-hydroxypropyl)benzenesulfonamide, N-ethyl-o-toluenesulfonamide, N-ethyl-p-toluenesulfonamide, o-toluenesulfonamide, and p-toluenesulfonamide, and more preferably N-butylbenzenesulfonamide.
[0079] In the present embodiment, in addition to the above, a plasticizer described in paragraph 0039 of Japanese Patent Application Laid-Open No. 07-011131 may be used, and the content thereof is incorporated into the present specification.
[0080] When the resin composition of the present embodiment includes a plasticizer, its content is preferably more than 1 mass part, more preferably more than 2 mass parts, more preferably more than 5 mass parts, and then more preferably more than 7 mass parts, and more preferably more than 9 mass parts, relative to 100 mass parts of resin composition. By being set to more than the aforementioned lower limit, there is a tendency for flexibility to improve. In addition, the upper limit of the content of the aforementioned plasticizer is preferably less than 30 mass parts, more preferably less than 25 mass parts, more preferably less than 20 mass parts, and then more preferably less than 15 mass parts, and more preferably less than 12 mass parts, relative to 100 mass parts of resin composition. By being set to less than the aforementioned upper limit, there is a tendency for surface appearance to further improve.
[0081] The resin composition of the present embodiment may contain only one plasticizer or two or more plasticizers. When containing two or more plasticizers, the total amount is preferably within the above range.
[0082] <Other ingredients>
[0083] The resin combination of the present embodiment may also include other components within the scope of the main purpose of the present invention. As such additives, reinforcing fillers (glass fiber, etc.), release agents, nucleating agents, light stabilizers, antioxidants, ultraviolet light absorbers, fluorescent brighteners, anti-dripping agents, antistatic agents, antifogging agents, anti-blocking agents, flowability improvers, dispersants, antibacterial agents, flame retardants, copper compounds, etc. may be cited.
[0084] In addition, in the resin composition of this embodiment, the content of the polyamide resin, the acid-modified polyolefin, and other additives is adjusted so that the total of each component becomes 100 mass %.
[0085] <Physical properties of resin composition>
[0086] The resin composition of the present embodiment is preferably excellent in flexibility. Specifically, the resin composition of the present embodiment is molded into an ISO multi-purpose dumbbell test piece (4 mm thick), and the flexural modulus measured at a temperature of 23 ° C according to ISO178 is preferably 3 GPa or less, more preferably 2.5 GPa or less, further preferably 2 GPa or less, and further preferably 1.5 GPa or less. Such a low flexural modulus is achieved by compounding an acid-modified polyolefin. The lower limit of the aforementioned flexural modulus is not particularly limited, and 0.1 GPa or more is practical.
[0087] The resin composition of the present embodiment preferably has a fast crystallization speed. Specifically, when the resin composition of the present embodiment is molded into an injection molded sheet with a thickness of 1 mmt at a mold temperature of 90° C. and crystallized, the molding cycle is preferably 50 seconds or less.
[0088] The resin composition of the present embodiment preferably has excellent resistance to cold and heat shock. Specifically, the resin composition of the present embodiment is molded into an ISO multi-purpose dumbbell test piece (4 mm thick), and the Charpy impact strength (notched, unit: kJ / m) at a temperature of -40°C according to ISO179 standard is 2 ) is preferably 8 kJ / m 2 More preferably, 10 kJ / m 2 More preferably, 15 kJ / m 2 More preferably, 20 kJ / m 2 There is no upper limit, but 50 kJ / m 2 The following is the actual result: Such high thermal shock resistance is achieved by using a predetermined xylylenediamine-based polyamide resin and blending it with an acid-modified polyolefin.
[0089] The details of the methods for measuring these physical properties are described in the examples described later.
[0090] <Method for producing resin composition>
[0091] The manufacture method of the resin combination of the present embodiment is not particularly limited, and is preferably a method using a single screw or twin screw extruder with a device capable of devolatilization from a vent as a mixing machine. The above-mentioned xylylenediamine-based polyamide resin, acid-modified polyolefin and other additives compounded as required can be supplied to the mixing machine together, or other compounding components can be supplied sequentially after the polyamide resin component is supplied. In addition, two or more components selected from each component can also be pre-mixed and mixed.
[0092] The method for producing a molded article using the resin composition of the present embodiment is not particularly limited, and molding methods commonly used for thermoplastic resins, i.e., injection molding, blow molding, extrusion molding, press molding, etc., can be applied. In this case, from the viewpoint of good fluidity, a particularly preferred molding method is injection molding. During injection molding, the resin temperature is preferably controlled to 200 to 310°C.
[0093] <Application>
[0094] The molded article of the present embodiment is formed from the resin composition of the present embodiment.
[0095] The molded product of this embodiment can be widely used as an extrusion molded product or an injection molded product.
[0096] The molded product of this embodiment can also be applied to various storage containers, electrical / electronic equipment parts, precision equipment parts, office automation (OA) equipment parts, home appliance parts, mechanical mechanism parts, vehicle mechanism parts, etc. From the viewpoint that it can be made into an article with excellent resistance to cold and heat shock, the molded product of this embodiment is particularly suitable for use in cold areas. Specifically, it is suitable for ski boots, soles, etc. In addition, from the viewpoint of high flexibility, high chemical resistance, and the ability to reduce the amount of leached matter, it is also suitable for hoses, tubes, hydrogen tanks, etc.
[0097] Example
[0098] Hereinafter, the present invention will be further specifically described by enumerating examples. The materials, usage amounts, ratios, processing contents, processing steps etc. shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.
[0099] When the measuring equipment used in the examples is difficult to obtain due to discontinuation of production or the like, other equipment having equivalent performance may be used for measurement.
[0100] 1. Raw materials
[0101] The following polyamide resins were used.
[0102] <Synthesis Example 1MP12(30)>
[0103] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 60 mol of 1,12-dodecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed thoroughly. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,12-dodecanedioic acid and form a uniform fluid state. Under stirring, 60 mol of p- / m-xylylenediamine, in which 30 mol% of the diamine components were p-xylylenediamine and 70 mol% were m-xylylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 240°C. In addition, the water distilled out while dropping p- / m-xylylenediamine was discharged to the outside of the system through the partial condenser and condenser. After the dropwise addition of p- / m-xylylenediamine was completed, the liquid temperature was maintained at 240°C and the reaction was continued for 10 minutes. After that, the pressure inside the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 250°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and cut into pellets after water cooling to obtain pellets of the melt polymer product.
[0104] The melting point of the obtained polyamide resin (MP12(30)) was 206°C.
[0105] <Synthesis Example 2 Synthesis of MP12 (40)>
[0106] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 60 mol of 1,12-dodecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed thoroughly. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,12-dodecanedioic acid and form a uniform fluid state. Under stirring, 60 mol of p- / m-xylylenediamine, in which 40 mol% of the diamine components were p-xylylenediamine and 60 mol% were m-xylylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 250°C. In addition, the water distilled while dropping p- / m-xylylenediamine was discharged to the outside of the system through the partial condenser and condenser. After the dropwise addition of p- / m-xylylenediamine was completed, the liquid temperature was maintained at 250°C and the reaction was continued for 10 minutes. After that, the pressure inside the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 260°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and cut into pellets after water cooling to obtain pellets of the melt polymerized product.
[0107] The melting point of the obtained polyamide resin (MP12(40)) was 216°C.
[0108] <Synthesis Example 3 Synthesis of MP14 (30)>
[0109] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 60 mol of 1,14-tetradecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed thoroughly. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,14-tetradecanedioic acid and form a uniform fluid state. Under stirring, 60 mol of p- / m-xylylenediamine, in which 30 mol% of the diamine components were p-xylylenediamine and 70 mol% were m-xylylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 240°C. In addition, the water distilled while dropping p- / m-xylylenediamine was discharged to the outside of the system through the partial condenser and condenser. After the dropwise addition of p- / m-xylylenediamine was completed, the liquid temperature was maintained at 240°C and the reaction was continued for 10 minutes. After that, the pressure inside the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 250°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and cut into pellets after water cooling to obtain pellets of the melt polymer product.
[0110] The melting point of the obtained polyamide resin (MP14(30)) was 200°C.
[0111] <Synthesis Example 4 Synthesis of MXD12>
[0112] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 60 mol of 1,12-dodecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed thoroughly. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,12-dodecanedioic acid and form a uniform fluid state. Under stirring, 60 mol of meta-xylylenediamine was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 230°C. In addition, the water distilled while dropping meta-xylylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of meta-xylylenediamine was completed, the liquid temperature was maintained at 230°C and the reaction was continued for 10 minutes. Thereafter, the internal pressure of the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 240°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of a strand, and then cut into pellets after water cooling to obtain pellets of a molten polymer product.
[0113] The melting point of the obtained polyamide resin (MXD12) was 186°C.
[0114] <Synthesis Example 5 Synthesis of PXD12>
[0115] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank, and a nitrogen inlet tube, 60 mol of 1,12-dodecanedioic acid was accurately weighed and placed, and nitrogen replacement was performed thoroughly. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve 1,12-dodecanedioic acid and form a uniform fluid state. Under stirring, 60 mol of p-phenylenediamine was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 290°C. In addition, the water distilled while dropping p-phenylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of p-phenylenediamine was completed, the liquid temperature was maintained at 290°C and the reaction was continued for 10 minutes. Thereafter, the internal pressure of the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 300°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of a strand, and then cut into pellets after water cooling to obtain pellets of a molten polymer product.
[0116] The melting point of the obtained polyamide resin (PXD12) was 269°C.
[0117] <Synthesis Example 7 Synthesis of MP10 (30)>
[0118] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank and a nitrogen inlet tube, 60 mol of sebacic acid was accurately weighed, and nitrogen replacement was fully performed. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve the sebacic acid and form a uniform flow state. Under stirring, 60 mol of p- / m-phenylenediamine, in which 30 mol% of the diamine components were p-phenylenediamine and 70 mol% were m-phenylenediamine, was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 250°C. In addition, the water distilled while dropping the p- / m-phenylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of the p- / m-phenylenediamine was completed, the liquid temperature was maintained at 250°C and the reaction was continued for 10 minutes. After that, the internal pressure of the reaction system was continuously reduced to 600 Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 260° C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of strands, and then cut into pellets after water cooling to obtain pellets of the melt polymer product.
[0119] The melting point of the obtained polyamide resin (MP10) was 215°C.
[0120] <Synthesis Example 8 Synthesis of MXD10>
[0121] In a jacketed reactor equipped with a stirrer, a partial condenser, a condenser, a thermometer, a dropping tank and a nitrogen inlet tube, 60 mol of sebacic acid was accurately weighed, and nitrogen substitution was fully performed. Then, the temperature was raised to 180°C under a small amount of nitrogen flow to dissolve the sebacic acid and form a uniform flow state. Under stirring, 60 mol of meta-xylylenediamine was added dropwise over 160 minutes. During this period, the internal pressure of the reaction system was set to normal pressure, and the internal temperature was continuously raised to 240°C. In addition, the water distilled while dropping meta-xylylenediamine was discharged to the outside of the system through the partial condenser and the condenser. After the dropwise addition of meta-xylylenediamine was completed, the liquid temperature was maintained at 240°C and the reaction was continued for 10 minutes. After that, the internal pressure of the reaction system was continuously reduced to 600Torr within 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 250°C. After the reaction was completed, a pressure of 0.3 MPa was applied to the reactor under nitrogen, and the polymer was taken out from the nozzle at the bottom of the polymerization tank in the form of a strand, and then cut into pellets after water cooling to obtain pellets of a molten polymer product.
[0122] The melting point of the obtained polyamide resin (MXD10) was 190°C.
[0123] PA6: Polyamide 6, manufactured by UBE, product number: UBE NYLON 1022B
[0124] PA12: Polyamide 12, manufactured by UBE, product number: UBESTA3024U
[0125] The following polyolefins and plasticizers were used.
[0126] MH5020: TAFMER MH5020, maleic anhydride-modified ethylene-butene copolymer, manufactured by Mitsui Chemicals, Inc., maleic anhydride modification rate: 1.0 mass%
[0127] MH5040: TAFMER MH5040, maleic anhydride-modified ethylene-butene copolymer, manufactured by Mitsui Chemicals, Inc., maleic anhydride modification rate: 2.0 mass%
[0128] Plasticizer: N-butylbenzenesulfonamide (BBSA), manufactured by Daihachi Chemical Industry Co., Ltd.
[0129] 2. Examples 1 to 11, Comparative Examples 1 to 4
[0130] <Compound>
[0131] Each component was weighed to give the composition shown in Tables 1 to 3 described below, blended in a drum, and fed from the bottom of a twin-screw extruder (TEM26SS, manufactured by Shibaura Machine Co., Ltd.) to melt and prepare pellets. The temperature of the twin-screw extruder was set at 240 to 280°C.
[0132] <Moldability>
[0133] When pellets were produced in a twin-screw extruder (TEM26SS, manufactured by Shibaura Machine Co., Ltd.), whether extrusion molding was possible was evaluated. For example, as a case where extrusion molding was not possible, for example, the resin extruded from the die head was broken before cooling.
[0134] Evaluation was performed as described below.
[0135] 5: Can be extruded.
[0136] 1: Cannot be extruded.
[0137] <Softness>
[0138] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours and then injection molded into ISO multi-purpose dumbbell test pieces (4 mm thick) in an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., "NEX140III") under the conditions of a barrel temperature of 200-300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds.
[0139] The flexural modulus (unit: GPa) was measured at a temperature of 23°C in accordance with ISO 178.
[0140] Evaluation was performed as described below.
[0141] 5: 1.5GPa or less
[0142] 4: More than 1.5 GPa and less than 2.0 GPa
[0143] 3: More than 2.0 GPa and less than 2.5 GPa
[0144] 2: More than 2.5 GPa and less than 3.0 GPa
[0145] 1: More than 3.0GPa
[0146] <Crystallization speed>
[0147] The pellets obtained by the above-mentioned production method were dried at 120°C for 4 hours and then injection molded into a three-stage plate in an injection molding machine (NEX140III manufactured by Nissei Plastic Industry Co., Ltd.) at a cylinder temperature of 200-300°C and a mold temperature of 90°C.
[0148] Evaluation was performed as described below.
[0149] 5: For a 1mm thick molded piece of a three-level plate, the molding cycle during crystallization in the mold is less than 50 seconds
[0150] 1: For a 1mm thick molded piece of a three-level plate, the molding cycle during crystallization in the mold is longer than 50 seconds
[0151] <Amount of dissolved matter>
[0152] In a film forming machine, the film was formed into a 100 μm film at a cylinder temperature of 200 to 300°C.
[0153] A 100 μm thick film was cut into 1.5 cm × 20 cm, and the mass of 30 sheets of film was measured and placed together in a 110 mL sample bottle. After that, a mixed solvent (15 mL) containing toluene (45% by volume), isooctane (45% by volume) and ethanol (10% by volume) was added, and the lid was closed. After being stored at 40°C for 200 hours, the solution was transferred to a beaker and allowed to stand for 1 day. After standing, suction filtration (filter paper: PTFE, pore size 0.2 μm) was performed to measure the mass of the solid elution obtained. The mass of the solid elution ÷ the mass of the film (mg / g) was taken as the amount of elution.
[0154] 5: 0.1mg / g or less
[0155] 4: More than 0.1 mg / g and less than 0.2 mg / g
[0156] 3: More than 0.2 mg / g and less than 0.3 mg / g
[0157] 2: More than 0.3 mg / g and less than 0.4 mg / g
[0158] 1: more than 0.4 mg / g
[0159] <Chemical resistance>
[0160] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours and then injection molded into ISO multi-purpose dumbbell test pieces (4 mm thick) in an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., "NEX140III") under the conditions of a barrel temperature of 200-300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds.
[0161] The flexural modulus (unit: GPa) was measured at a temperature of 23°C in accordance with ISO 178.
[0162] The sample was immersed in 10 mass % hydrochloric acid for 7 days, and the flexural modulus was measured again. The ratio (%) of the flexural modulus after the immersion in hydrochloric acid to the initial flexural modulus was taken as the flexural modulus retention rate.
[0163] Evaluation was performed as described below.
[0164] 5: More than 80%
[0165] 4: 70% or more and less than 80%
[0166] 3: 60% or more and less than 70%
[0167] 2: 50% or more and less than 60%
[0168] 1: Less than 50%
[0169] <Resistance to thermal shock>
[0170] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours and then injection molded into ISO multi-purpose dumbbell test pieces (4 mm thick) in an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., "NEX140III") under the conditions of a barrel temperature of 200-300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds.
[0171] According to ISO179 standard, Charpy impact strength (notched, unit: kJ / m 2 ) determination.
[0172] Evaluation was performed as described below.
[0173] 5: 20 kJ / m 2 above
[0174] 4: 15 kJ / m 2 Above and below 20kJ / m 2
[0175] 3: 10kJ / m 2 Above and below 15kJ / m 2
[0176] 2: 8kJ / m 2 Above and below 10kJ / m 2
[0177] 1: less than 8kJ / m 2
[0178] [Table 1]
[0179]
[0180] [Table 2]
[0181]
[0182] [Table 3]
[0183]
[0184] In Tables 1 to 3 above, the polyolefin content is the polyolefin content (mass %) when the total amount of the resin composition is 100 mass %. The plasticizer content is the plasticizer content (mass parts) when the total amount of the resin composition is 100 mass parts.
[0185] In the resin composition of the present embodiment, crystallization of the molded article was confirmed even when the mold temperature was 90° C. (Examples 1 to 11). Furthermore, a molded article excellent in flexibility, thermal shock resistance, gas barrier properties, etc. was obtained.
Claims
1. A resin composition comprising an acid-modified polyolefin in an amount of 0.1 to 50 parts by mass relative to 100 parts by mass of a polyamide resin, The polyamide resin includes a diamine unit and a dicarboxylic acid unit, wherein the diamine unit includes 70 mol % or more of a structural unit derived from xylylenediamine, and the dicarboxylic acid unit includes 70 mol % or more of a structural unit derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 11 to 20 carbon atoms.
2. The resin composition according to claim 1, wherein More than 70 mol % of the dicarboxylic acid units are derived from dodecanedioic acid and / or tetradecanedioic acid.
3. The resin composition according to claim 1, wherein More than 70 mol % of the dicarboxylic acid units are derived from dodecanedioic acid.
4. The resin composition according to any one of claims 1 to 3, wherein 20 to 100 mol % of the diamine units are derived from m-xylylenediamine, and 80 to 0 mol % are derived from p-xylylenediamine.
5. The resin composition according to claim 1, wherein More than 70 mol % of the dicarboxylic acid units are derived from dodecanedioic acid and / or tetradecanedioic acid, 20 to 100 mol % of the diamine units are derived from m-xylylenediamine, and 80 to 0 mol % are derived from p-xylylenediamine.
6. The resin composition according to any one of claims 1 to 5, wherein The acid-modified polyolefin comprises maleic anhydride-modified polyolefin. 7 . A molded article formed from the resin composition according to claim 1 .
Citation Information
Patent Citations
Polyamide resin composition
JP1995011131A
Polyamide resin composition
JP1997087475A
Resin composition, molded article, and method for producing molded article
JP2018087319A
Production method of polyamide resin
JP2018165298A